Accounts of PR Practices and Challenges by Senior Managers: A Qualitative Exploratory Study - Sheriko, Matthew (Université d'Ottawa / University of Ottawa, 2015)
Small nonprofit organizations are faced with limited resources and budgets for setting and reaching their goals. Some are nevertheless able to mitigate these challenges and achieve success. This thesis examines how this can be done. Organizations with excellent public relations programs have been found to be successful in achieving their goals (Grunig et al., 2002). Through the lens of the excellence model, this thesis analyzes, using in depth, semi-structured interview data, how senior managers of seven successful small nonprofits account for their success and address challenges as well as how their practices reflect the excellence model. This thesis does not test the excellence model in the context of small nonprofits, but rather attempts to establish recommendations for communication and PR success for small nonprofits based on what is learned from a small group of successful organizations.
Keywords: small nonprofit organizations; public relations; case study; excellence; qualitative interviews